Effect of Three Different Remineralizing Agents on Enamel Caries Formation – An in vitro Study - Sathe, N; Chakradhar, RVS Raju; Chandrasekhar, V (Kathmandu University Medical Journal, 2015)
Background Caries process is not a static one, but is dynamic with interspersed periods of demineralization and remineralization of enamel, intimately related and occurs episodically based upon the presence of cariogenic bacteria in dental plaque and the availability of refined carbohydrates for fermentation to organic acids. Objectives Early enamel caries could be reversed with avoidance of frank cavitation. The main objective of this study is to check whether enamel demineralization can be prevented by using the remineralizing agents. Method Forty freshly extracted human central incisors were selected and stored in saline at normal temperature. A window of 3 X 3mm enamel was created and all the specimens were then randomly divided into 4 groups of 10 each. Group I- teeth received no treatment, Group II- teeth treated with Acidulated Phosphate Flouride gel, Group III- teeth treated with Tooth Mousse Plus, Group IV- teeth treated with Remin+. Samples in all the groups were kept in artificial saliva for 24 hours and subjected to modified Ten Cate’s solution at an acidic pH of 3.5 for 10 days. The samples were sectioned and subjected to SEM evaluation. Result Scanning Electron Microscope(SEM) images showed decrease in pore volume of the enamel in all the treatment groups compared to the control group indicating increase in resistance to demineralization in acidic pH. Conclusion The three groups of remineralizing agents, Acidulated Phosphate Fluoride gel, Tooth Mousse Plus and Remin + showed significant increase in fluoride content and negligible increase in calcium content indicating there is remineraliztion. Kathmandu University Medical Journal Vol.12(1) 2014: 16-20